Status of the current COVID-19 vaccine candidates: Implications in the sau- di population (2020)
Aim The purpose of this review is to discuss the current status of local and international efforts undergoing clinical trials aiming at developing a Coronavirus Disease-2019 (COVID-19) vaccine, and to highlight the anticipated challenges of this vaccine globally and in Saudi Arabia. Present Findings COVID-19 vaccine development efforts started in early January 2020 when Chinese scientists shared the Coronavirus genomic sequence in public domain. Approximately 321 research groups initiated the search for a vaccine, out of which 41 have reached phase I/II trails and 11 reached phase-III clinical trials, including approved vaccines for early to limited use. Out of these projects are two labs in the Kingdom of Saudi Arabia still in early stages of development of a COVID-19 vaccine. Several vaccine attempts are being tested from traditional, attenuated virus methods, to new nucleic acid-based designs. However, no vaccine has yet completed clinical trials and reached public domain. In spite of the challenges faced during previous vaccine trials, researchers have found that Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2), the causative agent of COVID-19 is structurally similar to the (SARS-CoV-1) and the Middle Eastern Respiratory Syndrome Coronavirus (MERS-CoV), which caused epidemics in 2003 and 2012 respectively. Both SARS strains show identical affinity towards the type-II alveolar pneumocytes angiotensin converting enzyme-2 (ACE-2) receptor binding domains and therefore, similar pathogenicity. The race to develop the vaccine is predominantly for individuals at high risk of developing the infection, i.e. population groups who are most susceptible to experiencing fatal symptoms of the coronavirus. These include patients with comorbidities, above the age of 60 years and people at risk of contracting large viral loads, such as healthcare providers caring for critical admissions in inpatient wards, Intensive Care Units and Emergency Room settings. Summary Many different vaccine strategies are under development throughout different stages of the research timeline; however, it is estimated that none will show favorable results before end of 2020. For any immunization or interventional prevention/therapy system to reach the public and patients at high risk, it needs to undergo multiple phase trials to ensure safety and effectiveness. In this scoping review we aim to map the literature on COVID-19 vaccines and provide recommendations related to gaps in research, applicability and expected challenges for implementation of nationwide vaccination in Saudi Arabia.